Pendampingan Ibu Hamil Melalui Program Perencanaan Persalinan Dan Pencegahan Komplikasi (P4K) Di Desa Pondok Meja Kecamatan Mestong Kabupaten Muaro Jambi - Asparian Asparian; Willia Novita Eka Rini; Adelina Fitri (Jurnal Salam Sehat Masyarakat (JSSM), 2019)
ABSTRACT It is estimated that every day around 830 women die from preventable causes related to pregnancy and childbirth. Health programs to prevent maternal deaths can be implemented through the Childbirth Planning and Complications Prevention Program (P4K). Pregnancy easy workout can be done in planning a safe delivery and preparation in the face of possible complications during labor. The aim of community service is done to improve the skills of pregnancy exercises for pregnant women and Posyandu cadres so that the normal delivery and normal birth weight of the baby are obtained. This pregnancy easy workout activity partnered with the Village Government of Pondok Meja and Posyandu cadres in each village to attract community interest in doing pregnancy easy workout. Pregnancy easy workout improve the skills of mothers and Posyandu cadres in the context of planning birth and prevention of complications. Community service activities are able to attract pregnant women and Posyandu cadres to do pregnancy easy work out. It is hoped that going forward this pregnancy easy workout can be done continuously and sustainably.